2020
DOI: 10.1111/are.14478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental arginine supplementation on the growth, immunity and resistance of tilapia fingerlings to Streptococcus agalactiae

Abstract: Streptococcosis causes serious economic losses to fish farms every year. A four-week feeding trial was carried out to evaluate arginine (ARG) supplementation in the diet of Nile tilapia (Oreochromis niloticus) fingerlings challenged by Streptococcus agalactiae.Fish were fed with experimental diets containing five levels of supplementation with 1.39%, 1.76%, 1.97%, 2.18% or 2.39% analysed level of ARG. Each diet was randomly distributed in 30 tanks containing 20 fish/tank. After 30 days, no differences were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Haematological and biochemical evaluation of blood is important in assessing fish health with respect to dietary manipulation TA B L E 6 Biochemical and haematological parameters of GIFT tilapia juveniles fed graded levels of L-arginine (Metochis et al, 2017). Dietary arginine supplementation plays central role in the modulation of immune responses (Vianna et al, 2020). Arginine in the diet facilitates positive effects on both haematological and innate immune responses, such as haematocrit, haemoglobin, phagocytosis and circulating erythrocytes (Buentello et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Haematological and biochemical evaluation of blood is important in assessing fish health with respect to dietary manipulation TA B L E 6 Biochemical and haematological parameters of GIFT tilapia juveniles fed graded levels of L-arginine (Metochis et al, 2017). Dietary arginine supplementation plays central role in the modulation of immune responses (Vianna et al, 2020). Arginine in the diet facilitates positive effects on both haematological and innate immune responses, such as haematocrit, haemoglobin, phagocytosis and circulating erythrocytes (Buentello et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found dysregulation in arginine, tryptophan, and L-kynurenine. Arginine can affect cellular immunity under stress conditions [ 43 ]. Tryptophan is essential for protein synthesis and some physiological metabolic functions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary arginine supplementation from 2.10% to 3.82% also significantly enhanced the innate immune responses, and decreased the cumulative mortality rate of juvenile turbot infected with E. tarda ( Zhang et al., 2017 ). A reduction in the mortality rate of Nile tilapia fingerlings after Streptococcus agalactiae challenge and a boost in immune responses were observed in all supplementations of arginine (from 1.55% to 2.39%) in the diet ( Vianna et al., 2020 ). Dietary arginine supplementation (from 2.08% to 3.48%) also modulated nonspecific immune responses in Indian major carp ( Cirrhinus mrigala ) exposed to hypoxia and reduced its mortality after A. hydrophila infection ( Varghese et al., 2020 ).…”
Section: Arginine Immunonutrition In Fishmentioning
confidence: 96%